The Influence of Price and Service Quality on Gojek's Brand Image on Eka Prasetya's Students - Wahyu Sahputra (Outline Journal of Economic Studies, 2022)
This study aims to determine the effect of Service Price and Service Quality on Brand Image Gojek on Eka Prasetya Students. The population in this study were Eka Prasetya students as many as 941 respondents. The research sample in this study were 90 people with Slovin formula. The T-test results showed that price partially had a positive and significant effect on Brand Image Gojek for Eka Prasetya Students. The T-test results showed that the Service Quality of Services partially had a positive and significant effect on Brand Image Gojek for Eka Prasetya Students. The F-test results show that the Price and Service Quality variables simultaneously have a positive and significant effect on Brand Image Gojek for Eka Prasetya Students. The coefficient of determination test results (R2) shows that the Brand Imag variable can be explained by the Price and Service Quality variable and the rest is explained by other variables not included in the research model such as Promotion and Customer Loyalty.